THE ROLE OF FINANCIAL PERFORMANCE IN MEDIATION OF ENTERPRISE RISK MANAGEMENT AND CORPORATE VALUE - Subagio, Indra Sukma; Saraswati, Esti (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
This study aims to determine the effect of financial performance as a mediating variable between ERM and firm value. Using secondary data from all companies in the consumer goods sector for the period 2018-2020 as the research population. The variables used are ERM for independent, projected financial performance with ROA, and firm value with Tobins-Q. Based on data processing with path analysis, it is known that ERM has a positive effect on firm value. .while ERM does not significantly affect financial performance. Financial performance is able to have a positive and significant influence on firm value, but fails to mediate the relationship between ERM and firm value.